Problem of India's Future Constitution, And Allied Articles - Selected By Quaid-e-Azam & MRT ;Preface By Quaid-e-Azam ; Edited By Dr. Ghulam Kibriya (Karachi Toosy Foundation, 1992)
Articles previously published in 2 different books: India's problem of her future constitution, and Home study series number 2, during 1940-1941.
Keywords: India -- India -- Politics and Government -- 1919-1947